The Patterns Of Prescribing, Health Beliefs And Adherence To Statin Therapy Among Patients With High Cardiovascular Disease Risk And Health Care Providers’ Knowledge, Attitude, Barriers And Practice Regarding Cardiovascular Risk Assessment And Statin Therapy In Yemen - Al-Ashwal, Fahmi Yahya Ahmed (2022)
This study aimed to assess the rate, patterns, and appropriateness of statin therapy prescription among patients with clinical indications. Moreover, this study aimed to evaluate the association between the health belief model (HBM) factors and adherence to statins. Furthermore, it is meant to assess the physicians’ and pharmacists’ knowledge, attitude, barriers, and practices regarding the up-to-date guideline recommendations for atherosclerotic cardiovascular diseases (ASCVD) risk assessment and statin therapy.